Crises of Care: School Leaders and Narratives of Compassion Fatigue (Journal of Organizational Psychology, 2021)
This study examined school administrators’ experiences with compassion fatigue. This study described negative effects that empathy and compassion may have on school leaders. Results of this study may be used to provide insight into ways that school leaders experience compassion fatigue as they navigate through ethically and emotionally challenging events. Such insight can be used to inform those preparing to become school leaders, those who shape training programs for school leaders at both the pre-service and staff development level, and leaders themselves as they seek to understand the significant and complex effects of their experiences.
Keywords: organizational psychology; compassion fatigue, burnout, ethic of care, school leadership, narrative inquiry